Design of a Multi-sensor and Re-configurable Smart Node for the IoT - Alarcão, João Pedro Castro da Rocha de Meneses (2018)
The rapid deployment of the Internet of Things (IoT) is much dependent on the capacity of the IoT node to be able to self-adapt to the target application. With the increase of sensor networks and diversity of sensors available and with the increasing integration of multiple sensors in a sensor node, it is necessary to develop systems capable of handling all of these sensors with high level of flexibility. These may have different characteristics that provide quite distinct interface requirements, thus giving rise to the need for systems with re-configurable properties. With the implementation of sensor networks in places where energy supply is limited or non-existent, and in situations where technician intervention is expensive, there is a need to exchange conventional energy sources by methods of storage and harvesting of the energy present in the environment, where the sensor node is used (autonomous and renewable energy sources). This thesis will focus on the study and implementation of a family of re-configurable and multi-sensor IoT nodes with special emphasis on the energy storage and power management. It will also focus on the develop of a CAD tool in order to help in the design of CMOS circuits, for the purpose of integrating all the strategies here presented.